Arus Bebas Tenaga Kerja dalam Era Masyarakat Ekonomi ASEAN: Ancaman bagi Indonesia? - Stanislaus Risadi Apresian (Indonesian Perspective, 2016)
ASEAN Economic Community has been entered into force in December 31st, 2015. A free labour movement is one of major agendas to support the establishment of ASEAN as a single market and production base of ASEAN. This agenda becomes a hot debate since it can be an opportunity or threat for Indonesia. In fact, most of Indonesian people view it as a threat for Indonesia. On the contrary to that view, this research takes a clear position to support that a free labour movement is not a threat for Indonesia. This research is aimed to give a new perspective to see labour market liberalization in ASEAN not as a threat by giving new empirical findings. Theoritically, this research will give new empirical findings to explain that a free labour movement is not a threat for Indonesia by using liberal-institutionalis perspective. Practically, this research will give some policy recommendations addressed to the Government of Indonesia and other stakeholders related to employment issue.Keywords: ASEAN Economic Community, free labour movement, Indonesia